Numerical investigation of thermal performances of hybrid nanofluids in solar collectors implementing polygonal rough surfaces - B. Varun Kumar; P. Rajesh Kanna; R․H․B․ Ramamurthy; Dhinesh Balasubramanian; Utku Kale; Artūras Kilikevičius (Results in Engineering, 2025)
This study presents a CFD - simulation analysis of the thermal performance of hybrid nanofluids like multi-walled carbon nanotubes with Aluminium Oxide + water (MWCNT - Al2O3/H2O), aluminium oxide, and copper oxide with base water (Al2O3CuO/H2O) and aluminium oxide with base water (Al2O / H2O) in solar collectors with implementing forward faced polygonal shaped rough surfaces. The ribbed surface is arranged at a relative pitch distance of p/e = 5 and relative roughness height e/D = 0.2. The thermal performances are ascertained by Nusselt Number (Nu), friction factor (ƒ), and thermo-hydraulic performances (THP) by varying Reynolds Number (Re) ranging from Re 10,000 to Re 50,000. Hybrid nanofluids with forward-faced polygonal rough surfaces significantly enhance thermal efficiency, validated by selecting the RNG k-e turbulence model were compared with the Gnielinski equation for smooth surfaces. The research reveals that higher convective heat transfer has been attained in (Al2O3/H2O) with a 4 % volume concentration of hybrid nanofluid with the highest THP values of 1.16 at Al2O3/H2O with 1 % volume concentration in a lower Reynolds number. Besides, a significant thermal enhancement was recorded in solar collectors by using a hybrid nanofluid rather than water.